The satiety signaling neuropeptide perisulfakinin inhibits the activity of central neurons promoting general activity - Wicher, Dieter; Derst, Christian; Gautier, Hélène; Lapied, Bruno; Heinemann, Stefan H.; Agricola, Hans-jürgen (Frontiers in Cellular Neuroscience, 2007)
The metabolic state is one of the determinants of the general activity level. Satiety is related to resting or sleep whereas hunger correlates to wakefulness and activity. The counterpart to the mammalian satiety signal cholecystokinin (CCK) in insects are the sulfakinins. The aim of this study was to resolve the mechanism by which the antifeedant activity of perisulfakinin (PSK) in Periplaneta americana is mediated. We identified the sources of PSK which is used both as hormone and as paracrine messenger. PSK is found in the neurohemal organ of the brain and in nerve endings throughout the central nervous system. To correlate the distributions of PSK and its receptor (PSKR), we cloned the gene coding for PSKR and provide evidence for its expression within the nervous system. It occurs only in a few neurons, among them are the dorsal unpaired median (DUM) neurons which release octopamine thereby regulating the general level of activity. Application of PSK to DUM neurons attenuated the spiking frequency (EC50=11pM) due to reduction of a pacemaker Ca2+ current through cAMP-inhibited pTRPγ channels. PSK increased the intracellular cAMP level while decreasing the intracellular Ca2+ concentration in DUM neurons. Thus, the satiety signal conferred by PSK acts antagonistically to the hunger signal, provided by the adipokinetic hormone (AKH): PSK depresses the electrical activity of DUM neurons by inhibiting the pTRPγ channel that is activated by AKH under conditions of food shortage.